Multimodality standard of care treatment of resectable and borderline resectable pancreatic cancer - Neoptolemos, John P.; Ghaneh, Paula; Hackert, Thilo (Hepatobiliary surgery and nutrition, 2021)
Multimodality standard of care treatment of resectable and borderline resectable pancreatic cancer
Gesehen am 16.11.2021